Morphometrical analysis of the thoracolumbar dural sac in sheep using computed assisted myelography - Mageed, M.; Ionita, J.-C.; Ludewig, E.; Brehm, W.; Gerlach, K. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
Sheep are frequently used as animal models in experimental spinal injury studies. Therefore, extensive knowledge of ovine spinal dimensions is essential for experimental design and interpretation of results obtained in these trials. This study aimed to obtain quantitative morphometrical data of the thoracolumbar dural sac in sheep and determine the anatomical relationship between the dural sac and the vertebral canal.Computed assisted myelography imaging was carried out in five adult German Black-Headed Mutton sheep under general anaesthesia. Transverse images were acquired with 2 mm slice thickness from the first thoracic to the sixth lumbar vertebrae. Sagittal and transverse diameters and the cross-sectional area of the dural sac and vertebral canal were measured. To determine the anatomical relationship between the dural sac and vertebral canal, the pedicledural sac distance (PPSD) and the epidural space as well as the SAC (available space for the dural sac) were calculated.Sagittal diameters of the dural sac ranged from 5.1 to 12.0 mm. Transverse diameters ranged from 5.6 to 12.2 mm. The dural sac area covered 45.9% and 49.0% of the thoracic and lumbar vertebral canal area. The PDSD in the lumbar vertebrae was up to 15.8% larger than in the thoracic ones. The dural sac area was significantly positively correlated with the transverse diameter and area of the vertebral canal.The lumbar vertebral canal contained more space for the dural sac, which seems to be safer for testing spinal implants.
Keywords: Animal model; ovine; dural sac; myelography; computed tomography